KEBIJAKAN PEMERINTAH PUSAT DALAM PENERAPAN MORATORIUM DENGAN PEMEKARAN PAPUA - Sufrin Ridja; Hedwig Adianto Mau; Umar Suryadi Bakry (Jurnal Ilmiah Global Education, 2023)
The issues raised in this study are the division of D Papua and the implementation of the moratorium. Based on Law Number 23 of 2014 concerning Regional Government and Law Number 2 of 2021 concerning the Second Amendment to Law Number 21 of 2001 concerning Special Autonomy for the Province of  Papua for the implementation of this Law the government issued Government Regulation Number 106 of 2021 concerning the authority and institutional implementation of the special autonomy policy for the province of  Papua. In this research, Organ Theory and Legal Certainty Theory are used which will be the tools of analysis to dissect existing problems.